Hubungan antara Minat, dan Sikap Mahasiswa UNISMA Bekasi terhadap Aliran Islam Sempalan dan Ingkar Syariat dengan Perilaku Ibadah Mahasiswa - Yayat Suharyat (Turats, 2014)
This research topic is the relationship between the Interests, and Attitudes toward Students of Unisma Bekasi Flow islamic Shari'a dissenter Splinter and the Worship of Student Conduct. Based on the analysis results of this study concluded the following: First, there is a positive relationship between students' interest to splinter the flow behavior of the student worship. This suggests that if the interest of students towards Islam splinter flow increases, will also increase the student 's behavior deviates worship. If the low interest of students towards mainstream Islam splinter, then the student will conduct worship in accordance with applicable law. Second, there is a positive relationship between student attitudes toward Islam splinter the flow behavior of the student worship. This shows that if the student attitude toward Islam splinter improved flow, will increase as well worship deviant behavior (not Shari'a compliant) of students. Similarly, the lower the positive attitude of students towards mainstream Islam splinter, then the procedure decreases the tendency to deviate worship among the students. Third, there is a positive relationshipjointly between the interest ofstudents towards mainstream Islam splinter and student attitudes toward mainstream Islam splinter worship with deviant behavior (not Shari'a compliant) of students. This suggests that if the interest of students towards mainstream Islam splinter and student attitudes toward Islam splinter flow increased, so did the worship deviant behavior (not Shari'a compliant) of students. Similarly, the lower the interest and attitudes of students towards mainstream Islam splinter the better behavior of the student worship (Shari'a compliant outlined). It can be concluded that the increase in worship deviant behavior (not Shari'a compliant) of the students contributed to the flow of students through the interest of Islam splinter and positive attitude of students towards mainstream Islam splinter, either separately or together.